Cyclodextrin-threaded conjugated polyrotaxanes as insulated molecular wires with reduced interstrand interactions. - Cacialli, F; Wilson, J; Michels, J; Daniel, C; Silva, C; Friend, R; Severin, N; Samorì, P; Rabe, J; O'Connell, M; Taylor, P; Anderson, H (2002)
Control of intermolecular interactions is crucial to the exploitation of molecular semiconductors for both organic electronics and the viable manipulation and incorporation of single molecules into nano-engineered devices. Here we explore the properties of a class of materials that are engineered at a supramolecular level by threading a conjugated macromolecule, such as poly(para-phenylene), poly(4,4'-diphenylene vinylene) or polyfluorene through alpha- or beta-cyclodextrin rings, so as to reduce intermolecular interactions and solid-state packing effects that red-shift and partially quench the luminescence. Our approach preserves the fundamental semiconducting properties of the conjugated wires, and is effective at both increasing the photoluminescence efficiency and blue-shifting the emission of the conjugated cores, in the solid state, while still allowing charge-transport. We used the polymers to prepare single-layer light-emitting diodes with Ca and Al cathodes, and observed blue and green emission. The reduced tendency for polymer chains to aggregate allows solution-processing of individual polyrotaxane wires onto substrates, as revealed by scanning force microscopy.